(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The distribution of ostracods in the composed Langhian-Serravallian section of Ras il Pellegrin (Malta) has been studied quantitatively to define the evolution of both the assemblages and the palaeoenvironmental conditions. 99 samples have been examined at a stratigraphic distance of about 1 m. 78 species have been identified whose assemblages indicate an epibathyal environment and a sedimentation depth of 500-700 m. In particular, the almost continuous occurrence of the genus Oblitacythereis, which characterizes the water layer just above the psychrosphere, together with the absolute absence of the psychrospheric genus Agrenocythere confirm this interpretation. The sudden drop of both the simple diversity and abundance near the boundary "Upper Globigerina Limestone" - "Blue Clays" Formations, especially at the top of the succession, in our opinion may be due to the the decrease of dissolved bottom oxygen content as supported also by the Cytherellidae.